Age group differences in blubber fatty acid profiles in northern elephant seals (Mirounga angustirostris) - Kirkpatrick, Aaron W.; Crocker, Daniel E.; Kanatous, Shane B.; Smith, Kerri J.; Kienle, Sarah S.; Trumble, Stephen J. (Frontiers in Marine Science, 2022)
Northern elephant seals (Mirounga angustirostris), like many marine mammals, rely on internal lipid stores, specifically fatty acids (FAs) stored in the blubber layer, to meet metabolic needs. The energetic demands of northern elephant seals vary with ontogeny, as each life-history stage experiences different metabolic requirements due to development, growth, and breeding. To date, no comprehensive study has reported on changes in blubber FA profiles across northern elephant seal age groups or sex. Therefore, our objective was to determine how blubber FAs differ across ontogeny and sex in northern elephant seals. As a sexually dimorphic mammal, northern elephant seals go through sex-specific ontogenetic changes in morphology and physiology; we hypothesized that these changes would be reflected in their FAs profiles. To determine this, FAs profiles were compared from full blubber cores collected from 79 northern elephant seals across four age groups. We provide the first evidence of blubber fatty acids differing across ontogeny as NES transition from young, developing seals to mature fully developed adults. However, we did not find differences in blubber FAs profiles between the sexes. Monounsaturated fatty acids (MUFAs) are found in the highest proportions across all NES age classes and sexes, followed by SFAs and PUFAs; this highlights the important role MUFAs play in maintaining fluidity of the blubber layer and in thermoregulation. The individual FAs with the highest concentrations (C16:1, C18:1n9 and C16:0) in northern elephant seal blubber are similar to those in other marine mammals. Weaned pup FAs profiles were significantly different from all other age classes; adults and juveniles also showed age-specific differences. Specifically, weaned pups had the highest proportions of SFAs and the lowest proportions of PUFA, suggesting use of PUFAs to aid development. Each life history stage of NES is interconnected to previous and future stages, making FA accumulation, mobilization, and storage an important process throughout an individual’s life. Further, any changes to this process can have cascading consequences throughout ontogeny in this species. Future monitoring of the FA composition of blubber across age classes could potentially indicate the costs of different environmental changes on blubber storage in NES.